Vitamin D status and its associations with clinical and laboratory parameters in patients with Addison’s disease - Zawadzka, Karolina; Matwiej, Katarzyna; Sokołowski, Grzegorz; Trofimiuk-Müldner, Małgorzata; Skalniak, Anna; Hubalewska-Dydejczyk, Alicja (Folia Medica Cracoviensia, 2021)
Introduction: There is increasing evidence that several autoimmune diseases, as well as their activity, are associated with vitamin D (VD) deficiency. Our study aimed to evaluate the prevalence of VD insufficiency in patients with Addison’s disease (AD), as well as to evaluate associations between VD concentrations and various clinical and laboratory parameters of the disease. Materials and Methods: We retrospectively analyzed medical records of 31 adult patients diag-nosed with autoimmune Addison’s disease, in whom serum VD was measured. We assessed correlations between serum VD and various clinical and laboratory parameters. Results: 90.3% of AD patients had inadequate VD concentrations (<30 ng/mL), and 19.3% of them were found to be severely VD deficient (<10 ng/mL). Among assessed laboratory variables, only serum calcium concentrations significantly correlated with VD status (r = 0.53, p = 0.006). The mean serum VD con-centration was significantly lower in patients with severe fatigue (15.17 ± 8.41 vs 26.83 ± 12.29 ng/mL, p = 0.011) and limited exercise capacity (12.38 ± 6.9 vs 21.63 ± 10.87 ng/mL, p = 0.016). Conclusions: This study demonstrates a high prevalence of VD deficiency in AD patients, as well as the association between low VD concentrations with symptoms such as severe fatigue or limited exercise capacity. Further studies are needed to clarify if impaired VD status is a risk factor in the pathogenesis of AD and to assess if VD supplementation improves the quality of life of AD patients.
Keywords: primary adrenal insufficiency; Addison’s disease; vitamin D; autoimmunity